A Comparison between dietary effects of Cuminum cyminum essential oil and Cuminum cyminum essential oil, loaded with iron nanoparticles, on growth performance, immunity and antioxidant indicators of white leg shrimp (Litopenaeus vannamei). (21st June 2018) - Sheikh Asadi, M.; Gharaei, A.; Mirdar Harijani, J.; Arshadi, A.
Abstract: This study evaluates the effect of dietary cumin essential oil's (CEO) and cumin essential oil's loaded iron nanoparticles (CEO‐loaded NPs) on growth performance, haematological parameters and antioxidant status of white leg shrimp. Shrimps with the initial weight of 3.38 ± 0.014 g were allocated into 15 fibreglass tanks (300 L, 60 shrimps per tank) and were fed with five experimental diets containing 0 g/kg CEO (the control diet), 5 g/kg CEO, 10 g/kg CEO, 5 g/kg CEO‐NPs and 10 g/kg CEO‐NPs for 56 days. After 56 days of culture, the shrimps fed with CEO and CEO‐loaded NPs supplemented diets showed a more significant increase in growth performance ( p < .05) than in the control diet. Total haemocyte count (THC) value, large‐granule cells (LGC), hyaline cells (HC)%, superoxide dismutase (SOD) and Alkaline phosphatase (AKP) activity were significantly higher ( p < .05) in the shrimps fed with CEO and CEO‐loaded NPs supplemented diets than the shrimps fed with the control diet. Glutathione peroxidase (GPX) enzyme activities along with the glucose and cholesterol concentrations significantly decreased in the shrimps fed with the CEO and CEO‐loaded NPs supplemented diets more than those fed with the control diet. The results suggest that the dietary CEO‐loaded NPs can improve the growth performance, the health status and the antioxidant capacity of L . vannamei .